Global Cooperation and Economies of Recognition: The Case of NGOs - Volker M. Heins (University of Duisburg-Essen, Käte Hamburger Kolleg / Centre for Global Cooperation Research (KHK/GCR21), 2014)
Transnational non-governmental organizations (NGOs) are commonly regarded either as agents of empire or as manifestations of the progressive enlightenment of humankind. This paper takes a different view, arguing that they are best characterized as versatile factors of global cooperation across regional, ideological, and sectoral boundaries. Whilst recognizing that multilateral cooperation is sought not as an end in itself but as a means of intervening on behalf of oppressed groups who are engaged in struggles for recognition, I argue that the physical and psychological distance of many NGO activists from these struggles can distort patterns of cooperation and practices of recognition. I conclude that,far from simply being lauded as harbingers of a transnational, post-Westphalian democratic order, NGOs should be seen as the human face of the 'global rise of the unelected', with deeply paradoxical implications for the future of transnational governance.
urn:nbn:de:hbz:464-20150105-102248-7
Keywords: 320; Global Governance; International NGOs; Theories of Recognition; Practices of Intervention; Ethical Witnessing; Harm Conventions